Integrating Time-Dependent and Time-Independent Earthquake Recurrence Models for Fault-Based Seismic Hazard Assessment in the Lampung Region, Southern Sumatra - Rizki Wulandari; Yudha Styawan; Satria Bagus Prabowo (Program Studi Fisika Universitas Negeri Jakarta, 2026)
The Lampung region in southern Sumatra is exposed to significant seismic hazard due to its proximity to the Sunda megathrust and multiple active crustal faults. This study integrates time-independent (Poissonian) and time-dependent (Brownian Passage Time/BPT) earthquake recurrence models to evaluate fault-specific rupture probabilities and their implications for probabilistic seismic hazard assessment (PSHA). This approach systematically bridges the gap between traditional stationary models and the physical reality of seismic cycles, ensuring that the resulting hazard estimates reflect the current elapsed time since the last major rupture. Earthquake catalogs from USGS, BMKG, and historical sources were compiled for shallow events ( 50 km) between 1900–2023, and fault parameters were derived from national hazard maps and published geological studies. Recurrence intervals were estimated for 28 major fault segments across Sumatra, the Sunda Strait, and western Java. Results show strong temporal variability in seismic potential, with the Kumering South segment exhibiting the highest 50-year rupture probability (>50%) due to its elapsed time nearing the estimated recurrence interval. In contrast, segments such as Semangko West-A show markedly reduced short-term probability under the BPT model. PSHA simulations using OpenQuake reveal peak ground acceleration (PGA) values of 0.6–1.5 g for 2% exceedance in 50 years, indicating very high hazard levels in areas adjacent to the Sumatra Fault System. Incorporating time-dependent recurrence provides a more cycle-consistent spatial pattern compared to Poissonian results, reducing overestimation in early-cycle segments and enhancing hazard representation in late-cycle faults. While this study is constrained by uncertainties in historical recurrence intervals and fault slip-rates, these findings provide a more refined academic contribution to regional hazard characterization, supporting more robust risk mitigation strategies in Lampung Province.